Suboptimal health pregnant women are associated with increased oxidative stress and unbalanced pro- and antiangiogenic growth mediators: a cross-sectional study in a Ghanaian population. (2nd January 2020) - Anto, Enoch Odame; Roberts, Peter; Coall, David Antony; Adua, Eric; Turpin, Cornelius Archer; Tawiah, Augustine; Wang, Youxin; Wang, Wei
Abstract: Optimal oxidative stress (OS) is important throughout pregnancy; however, an increased OS may alter placental angiogenesis culminating in an imbalanced of angiogenic growth mediators (AGMs). Suboptimal Health Status (SHS), a physical state between health and disease, may be associated with increased OS and unbalanced AGMs. In this study, we explored the association between SHS, biomarkers of OS (BOS) and AGMs among normotensive pregnant women (NTN-PW) in a Ghanaian Suboptimal Health Cohort Study (GHOACS). This comparative GHOACS recruited 593 NTN-PW from the Komfo Anokye Teaching Hospital, Ghana. SHS was measured using a Suboptimal Health Status Questionnaire-25 (SHSQ-25). Along with the subjective SHS measure, objective BOS: 8-hydroxy-2-deoxyguanosine (8-OHdG), 8-epiprostaglandinF2 alpha (8-epi-PGF2α), total antioxidant capacity (TAC), and AGMs: vascular endothelial growth factor-A (VEGF-A), soluble fms-like tyrosine kinase receptor 1 (sFlt-1), placental growth factor (PIGF) and soluble endoglin (sEng) were evaluated. Compared to optimal health NTN-PW, levels of PlGF, VEGF-A and TAC were significantly ( p < 0.05) reduced and negatively associated with SHS whilst sEng, sFlt-1, 8-epiPGF2α, 8-OHdG, and combined ratios of sFlt-1/PlGF, 8-epiPGF2α/PlGF, 8-OHdG/PlGF, and sEng/PlGF were significantly increased and positively associated with SHS. The first quartile for PIGF (2.79-fold) and VEGF-A (5.35-fold), and the fourth quartile for sEng (4.31-fold), sFlt-1 (1.84-fold), 8-epiPGF2α (2.23-fold), 8-OHdG (1.90-fold) and urinary 8-OHdG (1.95-fold) were independently associated with SHS ( p < 0.05). SHS is associated with increased OS and unbalanced AGMs. Early identification of SHS-related OS and unbalanced AGMs may inform clinicians of the need for therapeutic options.